Analisis Kegiatan Pengadaan Barang Pada Proyek Perbaikan Kereta Api : Studi Kasus : PT. XYZ - Stevani Agatha Yudiantoro; Mega Cattleya PA Islami (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
XYZ is a company engaged in train repair and maintenance services. In the effort to repair trains, procurement of goods is the key to the success of repair activities. Procurement of window glass which was carried out in accordance with the procedures implemented experienced problems due to changes in quantity and price in the agreement that had been made. Through addendum documents, changes to previous agreements can be updated. So that these changes do not hamper goods procurement activities.